Coevolutionary dynamics in the grass-livestock social-ecological system of China’s alpine pastoral areas: A case study of the Qilian Mountains region in China - Ligan Cai; Junhao Zhao; Jian Chen (PLoS ONE, 2025)
Evaluating the dynamic co-evolution and feedback mechanisms within socio-ecological systems is crucial for determining the resilience and sustainability of environmental governance strategies. The grass-livestock system, as a complex entity encompassing livestock nutrition, foraging behavior, vegetation ecology, pastoralists’ economic income, and policy interventions, indicates that any change in a single element may trigger a chain reaction within the system. This paper uses a system dynamics approach to construct a simulation model of the grass-livestock system in alpine pastoral areas, simulating the long-term dynamic co-evolution of the socio-ecological system in the Qilian Mountains region of China. Four optimization schemes were proposed, and the synergistic development of the grass-livestock system in alpine pastoral areas under each scheme was simulated. The results show that, under the premise of sustainable use of grazing-based artificial grassland, the combination of reasonable use of fenced grasslands and cooperative management by pastoralists can effectively control livestock numbers, ensure pastoralists’ income, and maintain grassland quality within the next 20 years, thereby achieving coordinated socio-economic and ecological development. Additionally, optimizing feed supply can significantly improve grass production, livestock weight, and income. Therefore, it is recommended that alpine pastoral areas prioritize both grassland ecological management and development, adopt grassland restoration technologies, strengthen the management of artificial grasslands, set reasonable grazing bans, develop pastoralist cooperative organizations and design internal operational mechanisms.